Assessment Of Knowledge, Attitudes, Perception And Barriers Towards Pharmacovigilance Activities Among Community Pharmacists And Final Year Pharmacy Students In Malaysia. - Mahmod Elkalmi, Ramadan Mohamed (2010)

(untitled)
Tindak Balas Ubat Berbahaya (Adverse Drug Reactions, ADR) sering kali dikaitkan dengan kadar morbiditi dan mortaliti yang tinggi di serantau dunia.